Upaya Kepatuhan Kerjasama Pemerintah Indonesia dengan Wildlife Conservation Society terhadap CITES terkait Isu Perdagangan Ilegal Trenggiling di Indonesia - Wibowo, Beatrix Franscya Egidia Saraswati; Susiatiningsih, Hermini; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The illegal trade in pangolins that occurs in Indonesia is one of the environmental issues that is a concern for the Government of Indonesia. This issue has a very high level of urgency where the pangolin population is decreasing due to the high number of illegal pangolin trades that occur in Indonesia. Seeing this, the Government of Indonesia is collaborating with one of the international non-governmental organizations, namely the Wildlife Conservation Society (WCS). The collaboration started in 2009 and is based on an international regime, namely CITES. Through this collaboration, the Government of Indonesia and WCS have produced various implementations in the form of various work programs in accordance with the CITES Pangolin Resolution 17.10 policy. The purpose of this study is to analyze the implementation and compliance of the cooperation between the Government of Indonesia and WCS on CITES related to the issue of illegal trade in pangolins in Indonesia. This study will use Compliance Theory, Institutionalism Neoliberalism Theory, and International Regime Concepts. Based on the research conducted, the main argument of the author is that the cooperation between the Government of Indonesia and WCS complies with CITES. This form of compliance is demonstrated by the implementation and implementation of various work programs in accordance with the mandates in CITES Pangolin Resolution 17.10.